2016
DOI: 10.1021/jacs.6b10451
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ as a Hydride Donor and Reductant

Abstract: Reduced nicotinamide adenine dinucleotide (NADH) can generate a ruthenium-hydride intermediate that catalyzes the reduction of O to HO, which endows it with potent anticancer properties. A catalyst that could access a Ru-H intermediate using oxidized nicotinamide adenine dinucleotide (NAD) as the H source, however, could draw upon a supply of reducing equivalents 1000-fold more abundant than NADH, which would enable significantly greater HO production. Herein, it is demonstrated, using the reduction of ABTS to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Recently, the reduction of NAD + was studied from the viewpoint of its orientation at the solution or electrode interfaces. Studies showed that there is a perpendicular orientation of NAD + on a glassy carbon as determined from charge consumed on the application of a potential sweep and such is in good agreement with the sequence of chemical reactions (Santhanam and Elving, 1973;Htet and Tennyson, 2016). Figure 4 are different anodic waves for the oxidation of NADH in various electrodes including glassy carbon (GC), platinum (Pt), and gold (Au).…”
Section: Figure 4: Composite Representation Of the Voltammetricsupporting
confidence: 55%
See 2 more Smart Citations
“…Recently, the reduction of NAD + was studied from the viewpoint of its orientation at the solution or electrode interfaces. Studies showed that there is a perpendicular orientation of NAD + on a glassy carbon as determined from charge consumed on the application of a potential sweep and such is in good agreement with the sequence of chemical reactions (Santhanam and Elving, 1973;Htet and Tennyson, 2016). Figure 4 are different anodic waves for the oxidation of NADH in various electrodes including glassy carbon (GC), platinum (Pt), and gold (Au).…”
Section: Figure 4: Composite Representation Of the Voltammetricsupporting
confidence: 55%
“…The processes involved in the electrochemical reduction of NAD + and the electrochemical oxidation of its reduced form NADH are summarized in Figure 4. The process starts with a one-electron reduction of NAD + to give a free radical NAD • seen at the cathodic wave at approximately -1 V. The free radical NAD • dimerizes to form (NAD)₂ followed with the subsequent one-electron reduction to form NADH at a potential of -1.6 V (Elving et al, 1982;Htet and Tennyson, 2016). The dimer (NAD)₂ is oxidized to give NAD + at around -0.4 V. Furthermore, the (NAD)₂ can undergo a proton-assisted disproportionation to NAD + and NADH (Bresnahan and Elving, 1981;Huang and Liu, 2014).…”
Section: Figure 4: Composite Representation Of the Voltammetricmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this value was nearly identical to the O–H/D KIE of 1.45 measured with NAD + 21. Although H 2 O 2 and NAD + are structurally dissimilar, their O–H p K a values (11.6 for H 2 O 2 and 11.8 for NAD + ) are nearly identical,48,49 therefore their O–H bond polarizations will be highly conserved.…”
Section: Resultssupporting
confidence: 65%
“…We recently reported a Ru complex ( Ru1 , Scheme 1B) that catalyzed the 1e – reduction of ABTS˙ – (Scheme 1C) with biologically-relevant alcohols (ascorbate, glucose, NAD + , etc. , Scheme 1D) as terminal reductants 21,22. Importantly, ABTS˙ – undergoes 1e – reduction at a potential ( E 1/2 = +0.68 V vs. NHE) comparable to the ROS generated during oxidative stress,23–25 therefore the one-electron redox reactivity of ABTS˙ – can thermodynamically approximate the corresponding reactivity of oxidizing species in living systems.…”
Section: Introductionmentioning
confidence: 99%